Endometriosis of Groin Mimicking Neoplasm - Maharjan, P. B.; Makaju, R.; Makaju, S.; Dhakal, R.; Lama, B.; Basnet, D.; Dhakal, B. (Kathmandu University Medical Journal, 2021)
Endometriosis is principally a disease of women in active reproductive life. Although it is rare, foci of endometrial tissue may be seen in the bowel, the umbilicus, abdominal surgical scars and in the lungs. Inguinal endometriosis is challenging to the clinicians and pathologist and often diagnosed accidentally. We present a case of inguinal endometriosis mimicking neoplasm. A 40 year old woman presented with a swelling in the right inguinal region associated with cyclical pain. In view of presence of atypical cells in fine needle aspiration cytology, metastatic carcinoma was rendered as diagnosis. Histopathological examination revealed endometrial glands and stroma which was further confirmed by immunohistochemistry. Diagnosis of inguinal endometriosis is difficult and often challenging because of unusual site. The clinician must have high index of suspicion with any patient who has cyclical symptoms. A good history and physical examination can guide clinical diagnosis of endometriosis.